2015
DOI: 10.1007/s10803-015-2403-z
|View full text |Cite
|
Sign up to set email alerts
|

Community and Social Participation Among Individuals with Autism Spectrum Disorder Transitioning to Adulthood

Abstract: Individuals with Autism Spectrum Disorders (ASDs) are at increased risk for poor psychosocial outcomes as adults. We described community and social participation in adolescents with ASDs as they transitioned from adolescence to adulthood, and identified adolescent factors associated with community and social participation outcomes in adulthood. We performed a secondary data analysis of a nationally representative cohort using the National Longitudinal Transition Study 2 and observed a significant decrease in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 19 publications
4
56
0
5
Order By: Relevance
“…21 Postsecondary outcomes did not vary by high school urbanicity. 19,21,27 TAY had higher odds of postsecondary employment if their high school contacted a vocational rehabilitation representative during transition planning. 22 However, contact between high schools and postsecondary education institutions (eg, a 2-or 4-year college or vocational and/or technical school) was not a significant predictor of postsecondary education attendance.…”
Section: Institutional Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Postsecondary outcomes did not vary by high school urbanicity. 19,21,27 TAY had higher odds of postsecondary employment if their high school contacted a vocational rehabilitation representative during transition planning. 22 However, contact between high schools and postsecondary education institutions (eg, a 2-or 4-year college or vocational and/or technical school) was not a significant predictor of postsecondary education attendance.…”
Section: Institutional Levelmentioning
confidence: 99%
“…24 Some study authors found a positive relationship between parent income and postsecondary employment, educational attainment, and social engagement, 19, 21, 22, 25 -27, 31, 33, 36 whereas others found no significant association. 19,27,29,34,36,37 Lower parent income was associated with decreased access to services. 30 Parental educational attainment was significantly associated with youth postsecondary education attendance 21,37 and employment 22,25 but not with independent living or friendships.…”
Section: Family Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…It is still unclear whether youth with ASD experience more or less community participation if they also have ID. Positive associations between cognitive functioning and rates of community participation among youth and young adults with ASD are documented (Liptak et al 2011;Myers et al 2015;Orsmond et al 2013), although the inverse relationship has also been found (Taylor & Seltzer 2011;Shattuck et al 2011). Solish et al (2010) reported children with ASD (n = 65; ages 5-17 years) participated in significantly fewer social and recreational activities than typically developing peers (n = 90); however, no significant differences were found between children with ASD and children with ID without ASD (n = 30).…”
mentioning
confidence: 98%
“…; Myers et al . ; Orsmond et al . ), although the inverse relationship has also been found (Taylor & Seltzer ; Shattuck et al .…”
mentioning
confidence: 99%